Tourism destination image and its implications for destination branding and competitiveness: The case of the UK market in the Algarve - Custódio, Maria João Ferreira (2022)
This study develops and empirically tests a model of tourism destination image in different periods of time, namely in the pre/post-visit (measuring the tourist satisfaction) and the peak/off-peak (exploring the seasonality factor). It is applied to the UK market visiting the Algarve as a tourism destination. Its aim is to contribute towards a better conceptualization of destination branding and competitiveness practices. The existence of a gap in the literature related to the field of destination marketing strategies based on knowledge of destination images was the starting point for this research. This knowledge can improve the efficient allocation of resources, particularly in the context of increasing destination competitiveness and travellers’ limitations in terms of time and money. To empirically test the model, the research applies a mixed-methods approach based on semi-structured interviews conducted with tourist stakeholders within the Algarve and questionnaires applied to tourists who visit the destination. The findings suggest that the Algarve’s image tends to be differentiated in the pre/post-visit and in the peak/off-peak, which result in establishing important aspects to distinguish the marketing strategies. The segments of the first-time and the repeaters have different preferences and characteristics regarding the type of accommodation chosen, the return intention and age profile. The Algarve image modifications are connected with the type of booking the visitors opt to make the reservation, the return intentions, the willingness to recommend the Algarve to friends and relatives and if it is the first or repeat-visit. Generally, tourists do not recognise “administrative boundaries” but rather the entire destination of the Algarve. As a consequence, the competitiveness and branding approach to the region should be global, as defended in the literature. The results are considered an on-going process, where the stakeholders must be continuously involved due to the importance of their opinion to identify the main strengths and weaknesses of the Algarve as a tourism destination.